HUBUNGAN MOTIVASI DAN PARTISIPASI BELAJAR MAHASISWA PADA MATA KULIAH SISTEM INFORMASI GEOGRAFIS DI PROGRAM STUDI GEOGRAFI FKIP UNCEN - Tumober, Renny Threesje; Abrauw, Rudolf Doni; Hamokwarong, Ester Y. (Program Studi Manajemen Pendidikan FKIP Universitas Cenderawasih, 2023)
This study aims to determine the relationship between learning motivation and student participation in semester VI Class of 2019 in the Geographic Information Systems course with the hypothesis that if rcount ≥ rtable, then Ho is rejected and Ha is accepted, and if rcount ≤ rtable, then Ho is accepted and Ha is rejected. The method used in this research is quantitative research with correlational analysis of Pearson Product Moment (PPM), with a total sample of 40 students in this study. Based on the results of the normality test, linearity test, homogeneity test and Pearson Product Moment correlation test, the research results show that there is a fairly strong relationship between learning motivation and learning participation, because the results of tcount ≥ ttable are 0.512 ≥0.312, so it can be concluded that the research hypothesis mentioned at the beginning of this study was accepted.